2022
DOI: 10.1038/s41598-022-09183-z
|View full text |Cite
|
Sign up to set email alerts
|

Coating Ti6Al4V implants with nanocrystalline diamond functionalized with BMP-7 promotes extracellular matrix mineralization in vitro and faster osseointegration in vivo

Abstract: The present study investigates the effect of an oxidized nanocrystalline diamond (O-NCD) coating functionalized with bone morphogenetic protein 7 (BMP-7) on human osteoblast maturation and extracellular matrix mineralization in vitro and on new bone formation in vivo. The chemical structure and the morphology of the NCD coating and the adhesion, thickness and morphology of the superimposed BMP-7 layer have also been assessed. The material analysis proved synthesis of a conformal diamond coating with a fine nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…The human nontumor osteoblast (hFOB) cell line (hFOB 1.19, ATCC CRL-1137, Manassas, VA, USA) [ 33 ] and primary normal human osteoblasts (hOBs; Clonetic; Lonza, Basel, Switzerland) were used in the present study. To expand the hFOBs, cells were cultured and expanded in a 1:1 mixture of Ham’s F12 medium and Dulbecco’s modified Eagle’s medium (DMEM) containing 2.5-mM L-glutamine supplemented with 100-U/mL penicillin/streptomycin (Gibco BRL, Thermo Fisher Scientific, Waltham, MA, USA), 0.3-mg/mL G418, and 10% FBS [ 33 ]. The hFOBs were expanded at 34 °C in an atmosphere with 5% CO 2 , and the medium was changed every 2 days until a sufficient number of cells was detected [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The human nontumor osteoblast (hFOB) cell line (hFOB 1.19, ATCC CRL-1137, Manassas, VA, USA) [ 33 ] and primary normal human osteoblasts (hOBs; Clonetic; Lonza, Basel, Switzerland) were used in the present study. To expand the hFOBs, cells were cultured and expanded in a 1:1 mixture of Ham’s F12 medium and Dulbecco’s modified Eagle’s medium (DMEM) containing 2.5-mM L-glutamine supplemented with 100-U/mL penicillin/streptomycin (Gibco BRL, Thermo Fisher Scientific, Waltham, MA, USA), 0.3-mg/mL G418, and 10% FBS [ 33 ]. The hFOBs were expanded at 34 °C in an atmosphere with 5% CO 2 , and the medium was changed every 2 days until a sufficient number of cells was detected [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The surface functionalization with rmBMP-7 likely causes a burst release of the exogenous growth factor, providing an extracellular BMP-7 concentration within the range that has been shown to be inhibitory for osteogenic differentiation [ 26 , 27 , 28 ]. However, this simple functionalization strategy must be considered with caution in light of other successful ones using either minimal or much higher concentrations of BMP-7 [ 8 , 9 , 10 , 11 ] On the other hand, it permits estimating the challenges that arise when one tries to mimic the interfacial in vivo reality for the design of in vitro studies on cell response to organic coatings on Ti. Our results highlight that it is feasible to evaluate the interactions of pre-osteoblastic cells with a Ti surface, and likely those with other solid biomaterials, and more closely mimic the in vivo reality by integrating a physiological blood clot prior to cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…Bone morphogenetic protein 7 (BMP-7) has been used in functionalization studies of biomaterials, due to its recognized stimulatory effects on osteogenic activity under specific conditions and the permission for its use in humans by the Food and Drug Administration [ 8 , 9 ]. The strategies used to functionalize with BMP-7 involve modifications of the biomaterial surface chemistry and topography at a nanoscale, including those of metals [ 8 , 9 , 10 , 11 ]. In a previous initial study, we observed that the effects of providing 40 and 200 ng/mL of a recombinant mouse (rm) BMP-7 to osteoblastic cells grown on titanium (Ti) were modulated by the nanotopographic features of its surface, with an increased expression of the osteoblast markers osteopontin (OPN) and alkaline phosphatase (ALP), but without enhancement in the mineralized matrix formation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Present implants for bone regeneration include metals, , polymers or organics, , and bioceramics. , However, metallic implants tend to conduct heat which interferes with treatment. The main metals used for medical applications are pure titanium and its alloys (a+β alloys, Ti–6Al–4V, Ti–Al–Nb, and β-Ti alloys). , Ion release is another of the main disadvantages of CoCr alloys, titanium, and titanium alloys .…”
Section: Introductionmentioning
confidence: 99%